Pembentukan kelompok belajar berdasarkan sosiometri upaya meningkatkan kemampuan menyelesaikan soal cerita dalam matematika yang berkaitan dengan kehidupan sehari-hari - Edi Mulyana; Abdul Rosyid; Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
The Ability To Solve need to be improved, therefore learning must be interesting and fud. One day to improve student,s ability is through The Formation of Study Group Based On Sociometry. The research aims to know the learning process, improve the ability, and influence The Formation of Study Group Based On Sociometry in Solve stories In Mathematics. This research is Classroom Action Research. This subject in this research is the students of grade eight F SMPN 4 Kuningan. Semester II schools year 2016/2017. The sum of the student geometry grade eight Fare thirty-six students. This research is collaborative between researcher, headmaster and subject teacher. Data were collected through observation, field notes, interviews, and documentation. The validity of the data is checked by triangulation. The data were analyzed descriptively, qualitative flow model. The results of this study indicate that there is an increase in the ability of children through The Formation of Study Group Based On Sosiometry. Namely the improvement of student,s skill in solving the story of cycle I as big 80.00 %. The improvement of student,s skill in solving the story of cycle II as big 90.32 %. And the improvement of student,s skill in solving the story of cycle III as big 97.22 %. The conclusion of this study is The Formation of Study Group Based On Sociometry can improve the ability to solve math story problems